Windows 95 liferaft - Richardson, Ronny (MANNING, 1996)
This is the "lite" version of Windows 95 books for the lowest level of users.The text captures the true essence of what beginners need to know--no frills. Windows 95 Liferaft is ideally suited for people who buy a new computer withWindows 95 already installed.